Governing the Commodification of Abuse: Platform Liability and Double-Sanction Reform for CSAM in Indonesia - Jamaludin, Ahmad; Sari, Ratu Arti Wulan; Saputra, Dandi Ditia (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This article examines how Indonesian digital law addresses Child Sexual Abuse Material (CSAM) when abuse is circulated and monetized through platform-based infrastructures. It argues that the present regime addresses end users more directly than platform-enabled circulation and therefore misaligns liability with the digital organization of harm.Design/methods/approach – This article uses normative legal research with statute, case, conceptual, and comparative approaches. It analyzes Indonesian legislation, selected court decisions, enforcement records, and publicly available platform-policy materials, with functional comparison to the European Union’s Digital Services Act and the United Kingdom’s Online Safety Act. Mosco’s political economy of communication guides the conceptual analysis.Findings – The analysis identifies a bifurcated liability structure: individual offenders are addressed primarily through criminal sanctions, while platform accountability remains concentrated in administrative compliance and nominal fines. The DY case documents a direct linkage between paid access, platform infrastructure, and payment mechanisms in CSAM circulation. The analysis further finds that nominal sanctions are poorly aligned with platform scale and that digital access revocation remains legally unstable without explicit statutory grounding and proportionality safeguards.Research implications/limitations – This article is confined to publicly accessible legal and regulatory materials and adopts a doctrinal approach without empirical validation. Consequently, it does not interrogate how enforcement capacity, platform governance mechanisms, or digital access restrictions operate in practice or shape behavioural outcomes.Practical implications – The findings underscore the need to recalibrate child-protection regulation in digital environments through more differentiated sanctioning logics, enhanced audit and oversight capacity, and clearer doctrinal thresholds for platform liability. They further call for narrowly tailored, legally reviewable digital access restrictions that balance effective harm prevention with proportionality and due process guarantees.Originality/value – This article advances the legal scholarship on digital sexual exploitation by embedding a political economy perspective that foregrounds the structural role of platform infrastructures in organising harm. It introduces a theoretically grounded double-sanction framework that aligns turnover-based corporate liability with reviewable digital access revocation for repeat offenders, thereby reconfiguring the nexus between economic accountability and behavioural deterrence.Paper type Research paper